Tissue bioconcentration and effects of fluoxetine in zebrafish (Danio rerio) and red crucian cap (Carassius auratus) after short-term and long-term exposure. (August 2018) - Pan, Chenyuan; Yang, Ming; Xu, Hai; Xu, Bentuo; Jiang, Lihui; Wu, Minghong
Abstract: Fluoxetion (FLU) is an antidepressant pharmaceutical most commonly detected in the aquatic environment. The present study aims to elucidate the tissue accumulation and effects of FLU using two different fish models. First, the multiple effects and the FLU levels in fish, were examined in zebrafish ( Danio rerio ) embryos exposed to FLU concentrations (0, 0.1, 1, 10, 100, 1000 μg/L) from 4 h post-fertilization (hpf) until 120 hpf. Exposure to FLU accelerated heart rates, postponed hatching time, and increased swimming speed of fish. A dynamic response of acetylcholinesterase (AChE) activity was also displayed in the fish. Second, a 30-day exposure experiment using red crucian carp ( Carassius auratus ) was performed, and it found that the concentration of FLU in fish organs increased with increasing water concentrations, but the highest FLU bioconcentration was present in the lowest FLU exposure group (0.1 μg/L). Finally, 6 days of exposure to 0.1 μg/L of FLU followed by a 6-day clearance experiment was performed with both adult zebrafish and red crucian carp. The FLU levels in different fish organs increased as exposure time increased, but they sharply declined following the 6-day clearance. Correspondingly, the changes in brain AChE activity and in antioxidant parameters in the liver were consistent with the FLU levels in the fish organs. Our study provides fundamental data on the tissue accumulation and concentration-dependent effects in fish exposed to fluoxetine. Highlights: Fluoxetine (FLU) caused concentration-dependent effects in fish larvae. The effective concentration of FLU on fish in water was as low as 0.1 μg/L. FLU levels in fish organs were significantly correlated with its induced effects. The accumulation pattern in fish tissue should be used to assess risks of drugs.